2019
DOI: 10.1007/s13197-019-03623-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the storage quality of Tahitian limes (Citrus latifolia) by pre-storage UV-C irradiation

Abstract: UV-C (180-280 nm) has been shown to extend the postharvest shelf-life of many horticulture crops. In this study, Tahitian limes (Citrus latifolia) were exposed to 0, 3.4, 7.2 and 10.5 kJ m-2 UV-C then stored for 28 days in air at 10°C and 80% RH. Weight loss, peel colour, calyx abscission, ethylene production, respiration rate, total soluble solids (TSS), titratable acidity (TA) and acceptability index were assessed. The results showed that UV-C treatment maintained lime peel green colour and retained calyx at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
1
Order By: Relevance
“…On the other hand, there were no differences between UV-C doses on TSS content (Table 1). Similarly, UV-C illumination did not affect TSS content in lime (Pristijono et al, 2019), pineapple (Sari et al, 2016), apple (Hemmaty et al, 2007), strawberry (Cote et al, 2013) and tomato (Liu et al, 2009).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, there were no differences between UV-C doses on TSS content (Table 1). Similarly, UV-C illumination did not affect TSS content in lime (Pristijono et al, 2019), pineapple (Sari et al, 2016), apple (Hemmaty et al, 2007), strawberry (Cote et al, 2013) and tomato (Liu et al, 2009).…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, many researchers reported that UV-C illumination reduced the decay rate or disease incidence in a variety of products such as peach (Abdipour et al, 2019) strawberry (Erkan et al, 2008), persimmon (Khademi et al, 2013), red pepper (Rodoni et al, 2015) and pineapple (Sari et al, 2016). In addition, UV-C illuminated limes had more acceptability index than control fruits after 28 days of storage (Pristijono et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, blue light can reduce the vitality of mold and impair its ability to infect fruit [ 19 ]. Treatment with UV-C at 180–280 nm and 10.5 kJ m −2 was found to maintain low ethylene production and respiration rate in lime fruit after 28 d of storage [ 30 ], while application of an alternating magnetic field inhibited the respiration of banana fruit [ 31 ]. These studies have confirmed the biological effects of physical handling technologies on postharvest fruit during storage, but the underlying physiological and metabolic mechanisms of fruits’ response to physical treatments need to be clarified in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were previously reported by Barka et al [40], who demonstrated the effect of UV-C irradiation (254 nm) on cell wall degradation enzymes, which led to a delay in fruit ripening and senescence process. The application of UV-C irradiation before storage, with a dose ranging from 3.4 to 10.5 kJ m -2 , helped preserve the quality of lime fruits during storage [41]. In addition, UV-C technology has been extensively studied as an alternative pasteurization treatment and extension of beverage shelf life [42].…”
Section: Preliminary Irradiation Test On Lemonsmentioning
confidence: 99%